Electrochemical-thermal behaviors of retired power lithium-ion batteries during high-temperature and overcharge/over-discharge cycles - Caisheng Li; Xianqing Liu; Changhong Wang; Lisheng Ye; Tingting Wu; Zhixuan Liang; Zejie Zhang; Ying Zeng; Kaizhe Li (Case Studies in Thermal Engineering, 2024)
To safely utilize retired power lithium-ion batteries (PLIBs) for secondary, LiFePO₄/graphite batteries were taken as research object. The electrochemical-thermal behaviors were investigated under different operating conditions. The experimental results show that heat generated will greatly increase, and the uneven distribution of temperature within the battery will become more severe during high-temperature cycles. Compared with room temperature cycling, the decay rate of battery SOH increased by 419.88 % after 400 cycles at high-temperature environment. After 400 cycles at 25 °C and 55 °C, the maximum temperature difference for 3C increased from 2.05 °C to 2.91 °C and 2.14 °C–3.03 °C, respectively, corresponding to the increases of 41.95 % and 41.59 %. After 800 cycles of overcharging, the battery state of health (SOH) was only 67.52 %; compared with the normal cycles, the decay rate increased by 156.25 %. Finally, a method for assessing the battery's health status based on the frequency of the peak area in the probability density function (PDF) was proposed. These results proved the effectiveness of the proposed method for evaluating the health of retired PLIBs.